HYDROGEOLOGICAL INTERPRETATION AND POTENTIAL OF THE NEW MAGNETIC RESONANCE SOUNDING (MRS) METHOD - Lubczynski M.; Roy J. (My University, 2003)
This study reviews the up-to-date hydrogeological contribution of the new, geophysical magnetic resonance sounding (MRS) method and presents new interpretation ideas and potential regarding various hydrogeological applications. The main advantage of the MRS method as compared to other geophysical methods is in its water selectivity. MRS is commercially available but is also the subject of R & D to minimize a number of limitations related not only to data acquisition but also to hydrogeological data interpretation. The two main MRS output data types are free water content (ΦMRS) and decay time constant (Td). Relations between ΦMRS and effective porosity, specific yield and specific storage are discussed in the framework of an original groundwater storage concept. Td is correlated empirically with hydraulic conductivity, however such correlation is not yet quantified for various rock types so Td has to be calibrated by borehole data. As an improvement of the data interpretation, a proposal of a new, multi-decay approach is presented. The advantage of such analysis is that it combines storage and flow property characteristics in assessing water content at various pore size fractions, and the disadvantage is that it is applicable only at large signal to noise ratios. Five case examples are used to show that combined interpretation of ΦMRS and Td can be used to evaluate subsurface hydrostratigraphy although such analysis is vulnerable to equivalence error and its resolution decreases with depth. MRS with large volume-averaging schema and current limitation to 1D approach is already suitable for groundwater modelling applications and for evaluation of groundwater potential in the MRS measurement scale (∼100×100 m2) but is not yet optimized for well siting. MRS can detect water in the unsaturated zone, which can be potentially used in real time subsurface flux monitoring. Field experiments indicate that MRS is not appropriate for groundwater salinity detection. No field experiments have yet been made to detect hydrogenated compounds like hydrocarbons and tracers in the subsurface.
Keywords: Magnetic resonance sounding; Hydrogeological interpretation; Aquifer storage; Hydraulic conductivity; Groundwater potential